Global hotspots and prospects of perimenopausal depression: A bibliometric analysis via CiteSpace - Gao, Mingzhou; Zhang, Hao; Gao, Zhan; Sun, Ya; Wang, Jieqiong; Wei, Fengqin; Gao, Dongmei (Frontiers in Psychiatry, 2022)
Background: Perimenopausal depression (PMD) is characterized by affective symptoms as well as menopause-specific somatic complaints and has attracted increasing attention over the past few decades. Using a bibliometric tool, this study aims to evaluate the origin, current hotspots, and research trends on perimenopausal depression. Methods: Articles with research on perimenopausal depression were retrieved from Web of Science Core Collection (WoSCC). We used the bibliometric method to analyse publication years, journals, countries, institutions, authors, research hotspots, and trends. We plotted the reference co-citation network and used keywords to analyse the research hotspots and trends. Results: A total of 209 publications related to PMD were identified from Web of Science Core Collection on May 8, 2022. The number of publications concerning PMD every year shows an upward trend. Further analysis indicated that 209 articles were contributed by 45 countries, 288 institutions, and 501 authors. The USA contributed the most significant number of publications, followed by China. Harvard University is the core institution of PMD research, and Cohen’s work has had an important impact on another research. The occurrence and pathological mechanisms of depression during the menopausal transition from the knowledge base of PMD. All of them belong to the category of gynecology and psychosis, which reflects the focus of the research topics. Major depression, postmenopausal women, symptoms like hot flashes, and prevalence and risk factors are research hotspots in PMD field. The frontiers in PMD field that will impact future research are anxiety, meta-analysis, association, and inventory. Conclusions: These findings provide us with the core countries, institutions, and authors in PMD research and point out the direction of attention in this field. Major depression, postmenopausal women, symptoms like hot flashes, and prevalence and risk factors focus on current studies. Future research hotspots will focus on anxiety, meta-analysis, association, and inventory.